Checklist of Butterfly Fauna From Kabal, Swat, Pakistan - Perveen, Farzana; Khan, Anzela (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
The butterflies are beautiful creature of nature with great economic importance as pollinator as well as bio-indicator of environments. The present survey was conducted to determine the characteristics of butterfly fauna from Kabal, Swat, Pakistan during March-June 2013. The study area was divided into 4 quadrates. A total of 170 specimens were collected of 13 species, falling in 10 genera and were identified belonging to 3 different families. The species identified, the Indian fritillary, Argynnis hyperbius; painted lady, Cynthia cardui; blue pansy, Junonia orithya; plain tiger, Danaus chrysippus; common leopard, Phalantha phalantha and common sailor, Neptis hylas were belonging to family Nymphalidae. The great black mormon, Papilio memnon; Chinese peacock black swallowtail emerald, Papilio bianor; dingy swallowtail, Papilio anactus and lime butterfly, Papilio demoleus were belonging to family Papilionidae. The common grass yellow, Eumera hecab; little orange tip, Coloti etrida and Murree green-veined white, Pieris ajaka were belonging to family Pieridae. Butterfly fauna from Kabal have been presented here for awareness, education and research. Proper preventive measures should be taken in order to minimize the natural habitat loss, as butterfly fauna is dependent upon proper environmental conditions.